Changes in morbidity and mortality during comprehensive community programme to control cardiovascular diseases during 1972-7 in North Karelia. Issue 6199 (10th November 1979) - Salonen, J T; Puska, P; Mustaniemi, H
Abstract : A comprehensive community programme studying the control of cardiovascular diseases (CVD) was carried out in North Karelia, Finland, between 1972 and 1977. The main objective was to reduce the mortality and morbidity of CVD, particularly in middle-aged men. Changes in the mortality and incidence of CVD were monitored by community-based registers of cases of acute myocardial infarction (AMI) and stroke and data on death certificates. During the programme the total mortality in the area decreased by 5% and the mortality from CVD decreased by 13% among men and 31% among women aged 30-64 years. The incidence of AMI fell by 16% among men and 5% among women, while that of cerebral stroke fell by 38% among men and 50% among women. Changes in mortality in North Karelia were compared with those in a matched control area; the difference between the two areas was not significant. The true effect of the programme cannot be deduced from these results, but mortality from CVD and the incidence of AMI and stroke fell during the five years studied. Thus the changes in mortality and morbidity of CVD accorded with the initial objectives of the programme.